KRAS mutations testing in non-small cell lung cancer: the role of Liquid biopsy in the basal setting - Nacchio, Mariantonia (J Thorac Dis, 2020)
In advanced stage non-small cell lung cancer (NSCLC) patients, Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) testing may soon acquire a predictive significance to select patients for AMG510 treatment. Since tissue samples are not always available, liquid biopsy may represent a viable option for KRAS testing. Here, we review the last three years clinical practice performed on 194 plasma based liquid biopsies by next generation sequencing (NGS) SiRe(®) panel. In particular, 36 (18.6%) KRAS mutated cases were identified, with an overall median allelic frequency of 5.0% (ranging between 0.2% and 46.8%). No concomitant mutations were observed in the other NSCLC clinical relevant genes included in the SiRe(®) panel, such as epidermal growth factor receptor (EGFR) and v-Raf murine sarcoma viral oncogene homolog B (BRAF). Exon 2 p.G12C was the most common detected mutation (13/36, 36.1%). In conclusion, our data update and confirm that SiRe(®) NGS panel represents a robust analytical tool to assess KRAS mutational status on circulating tumor DNA. Further investigation is required to design more cost-effective diagnostic algorithms to harmonize clinical relevant biomarker testing on tissue and blood in advanced stage NSCLC clinical practice.